Analisis Kinerja Daerah Aliran Sungai Unda Berdasarkan Indikator Penggunaan Lahan dan Debit Air - NI NYOMAN ARI PUTRI MURTIYAH; I NYOMAN SUNARTA; I WAYAN DIARA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Analysis of Unda Watershed Perfomanced Based on Land Use and Water Discharge Indicators The Unda watershed has experienced a decline in forest area, a decline in water catchment areas, an increase in residential areas and is known to have potential flooding. If the function of a watershed is disrupted, the hydrological system will be disrupted. The purpose of this study was to analyze changes in land use, water discharge and to know the performance of the Unda watershed which includes the precentage of vegetation cover, coefficient of flow regim and annual flow coefficient. The research method is descriptive comparative, by comparing the two parameters, namely the land use and water discharge in 2007, 2011 and 2016. The results showed that land use in Unda watershed were dominated by fields, forests, paddy fields, gardens, shrubs, settlement and open field. During the 2007-2016 period, the highest water discharge occurred in November 2016 amounting to 7.78 m3/sec while the lowest water discharge occurred in March 2011 amounting to 1.72 m3/sec. The results of watershed performance analysis based on indicators of percentage of vegetation cover indicate that the Unda watershed is at a medium level of damage and tends to deteriorate with a range of values ??of 41.42 - 22.63%, while in the flow regime coefficient indicator and annual flow coefficient, indicates that the Unda watershed is at a medium level of damage. The flow regime coefficient value of the 2007-2016 period is at a value of 9.81 - 1.65, then the annual flow coefficient value is at the value of 0.17 - 0.36%. Further research needs to be done regarding the assessment of watershed performance based on other indicators so that the performance of the Unda watershed is known from all aspects.